Optical properties of silicon nanocrystals embedded in a SiO2 matrix - Ding, Liang (2010)
Optical properties of isolated silicon nanocrystals (nc-Si) with a mean size of ∼4 nm embedded in a SiO2 matrix that was synthesized with an ion beam technique have been determined with spectroscopic ellipsometry in the photon energy range of 1.1–5.0 eV. The optical properties of the nc-Si are found to be well described by both the Lorentz oscillator model and the Forouhi-Bloomer (FB) model. The nc-Si exhibits a significant reduction in the dielectric functions and optical constants and a large blueshift (∼0.6 eV) in the absorption spectrum as compared with bulk crystalline silicon. The band gap of the nc-Si obtained from the FB model is ∼1.7 eV, showing a large band gap expansion of ∼0.6 eV relative to the bulk value. The band gap expansion is in very good agreement with the first-principles calculation of the nc-Si optical gap based on quantum confinement.